Eyes on the ball: screening football in East German cinema. Issue 1 (2nd January 2017) - McDougall, Alan
ABSTRACT: In communist East Germany, football was far more popular than the Olympic sports on which the country based its formidable sporting reputation. Very few of the films made by the state film studio Deutsche Film-Aktiengesellschaft (DEFA), though, took football as their subject matter – and those that did have been all but ignored by scholars of East German cinema. Focusing on two little-known works, the children's film Der neue Fimmel/The New Craze (1960) and the comedy Verzeihung, Sehen Sie Fußball?/Excuse Me, Are You Watching Football? (1983), this article examines the football film's evolving role as a marker of socialist values in East Germany. By analysing key themes in the two films, it argues that they chronicle a story of declining public faith in the cause of state socialism. DEFA's football films reflect and represent broad shifts in East German society in this period, charting transitions from the collective to the individual, from playing the game to watching it, and from an engagement with building socialism to a retreat from ideology to private concerns.